Wenshen Jianpi recipe, a blended traditional Chinese medicine, ameliorates proteinuria and renal injury in a rat model of diabetic nephropathy - Xiaodan Cao; Renxiong Wei; Jun Zhou; Xiaoxia Zhang; Wenbo Gong; Tinglong Jin; Xiabo Chen (BMC, 2019)
Abstract Background Wenshen Jianpi recipe (WSJPR), a blended traditional Chinese medicine, is considered to have the possible beneficial effect on the progression of diabetic nephropathy (DN). This present study was designed to elucidate this protective activity in a rat model with streptozotocin (STZ)-induced DN and to explore the possible underlying mechanism. Methods Adult Sprague Dawley (SD) rats were induced to develop DN through intraperitoneal injection of STZ (60 mg/kg). Animals were orally administered saline, WSJPR at 7.5, 15, 30 g/kg, and valsartan (25 mg/kg) daily for 8 weeks. Blood and 24-h urine samples of each rat were collected for biochemical examination at 2-week intervals. Microcirculatory blood flow in the renal cortex and hemorheology index were also measured. At the end of 8 weeks, all rats were sacrificed to obtain the kidney tissues for histological examination and reverse transcription polymerase chain reaction (RT-PCR) was used to analyze the transcriptional levels of nephrin and podocin genes. Results WSJPR could improve serum total protein (TP) and albumin (ALB), reduce the excretion rates of urine-TP (U-TP), urine-ALB (U-ALB) and urine urea nitrogen (UUN) (P < 0.05), although it did not significantly alter the hyperglycemia. In addition, treatment with WSJPR could strongly reduce blood flow, erythrocyte aggregation index, and ameliorate microcirculation. In histological measurement, WSJPR-treated rats showed a significant amelioration in glomerular hypertrophy and mesangial expansion. By RT-PCR, we found WSJPR up-regulated the nephrin and podocin expression at mRNA levels. Conclusion This study suggested that WSJPR could effectively relieve renal damage and improve renal function of DN rats by ameliorating metabolism disorder and increasing the gene expression of nephrin and podocin, which might be a useful approach for the treatment of DN.